2017
DOI: 10.1007/s00253-016-8087-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and metabolome responses of Shewanella oneidensis MR-1 to methyl orange under microaerophilic and aerobic conditions

Abstract: Shewanella oneidensis MR-1 degrades various azo dyes under microaerophilic and anaerobic conditions, but this process is inhibited under aerobic conditions. The mechanisms underlying azo dye biodegradation and inhibition remain unknown. Therefore, we investigated metabolic and transcriptional changes in strain MR-1, which was cultured under different conditions, to elucidate these mechanisms. At the transcriptional level, genes involved in certain metabolic processes, particularly the tricarboxylic acid (TCA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…In the presence of S. oneidensis MR-1, a slightly decreasing trend in the concentration of Orange G in the solution and a gently increasing trend in aniline concentration in the suspension with increasing incubation time were observed (Figure 2 and Figure 4). These results indicated that S. oneidensis MR-1 is a kind of Fe-reducing bacteria that has the potential to reduce Orange G to aniline, which is consistent with the previous viewpoint [29,30]. In the presence of S. oneidensis MR-1 and biochar, the removal rate of Orange G in the solution significantly accelerated (Figure 3B).…”
Section: Resultssupporting
confidence: 91%
“…In the presence of S. oneidensis MR-1, a slightly decreasing trend in the concentration of Orange G in the solution and a gently increasing trend in aniline concentration in the suspension with increasing incubation time were observed (Figure 2 and Figure 4). These results indicated that S. oneidensis MR-1 is a kind of Fe-reducing bacteria that has the potential to reduce Orange G to aniline, which is consistent with the previous viewpoint [29,30]. In the presence of S. oneidensis MR-1 and biochar, the removal rate of Orange G in the solution significantly accelerated (Figure 3B).…”
Section: Resultssupporting
confidence: 91%
“…Azoreductase gene has been shown to be regulated in different ways in different organisms and there seems to be no common pattern. Chen et al reported constitutive expression of azoreductase in Staphylococcus aureus , 29 while azoreductase expression is significantly induced in Shewanella oneidensis upon exposure to methyl orange 30 . The effect of azo dye exposure on azoreductase expression is not yet reported in Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Although several oxygen‐insensitive azoreductases have been reported until date, some enzymes like AzoR from S. oneidensis MR‐1 function only under microaerophilic to anaerobic conditions 30 . As azoreductase catalyzes reductive metabolism, it is plausible that a reducing environment may enhance its activity, even for oxygen‐insensitive enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Peak areas were normalized to culture optical densities ( 5 , 20 ). The concentrations of 60 metabolites related to essential metabolism were calculated using the concentration of each standard substrate.…”
Section: Methodsmentioning
confidence: 99%